Lysenkoism and the Population Control Movement - Simon, Julian L (Universidad de Costa Rica, 1997)
The case of Lysenkoism in the Soviet Uníon helps us understand how people's wrong beliefs can be influenced by what the information they receive from outside, especially when there is a large volume of media coverage and there is no contrary information to be heard. The population control movement in contemporary Umted States has many parallels lo the Lysenko episode.